2022
DOI: 10.1002/kjm2.12588
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐494‐3p facilitates the progression of bladder cancer by mediating the KLF9/RGS2 axis

Abstract: Bladder cancer (BC) is a familiar malignancy with high morbidity and mortality. The effect of treatment is unsatisfactory after the metastasis and invasion of BC. Hence, more studies should be carried out to explore the metastasis of BC. RT‐qPCR or/and western blot was conducted to evaluate miR‐494‐3p, KLF9, and RGS2 expression. Cell proliferation and invasion were estimated by MTT assay and transwell assay, respectively. Cell migration was tested by wound healing assay and transwell assay. Dual‐luciferase rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…However, when it comes to its interaction with miRNAs, most studies are illustrative of miRNAs‐mediated negative regulation of KLF9. A case in point is that miR‐494‐3p is the upstream gene that represses KLF9 expression in bladder cancer 39 . By contrast, our study initially identified that miR‐494‐3p was a downstream target of KLF9 and KLF9 positively regulated miR‐494‐3p.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…However, when it comes to its interaction with miRNAs, most studies are illustrative of miRNAs‐mediated negative regulation of KLF9. A case in point is that miR‐494‐3p is the upstream gene that represses KLF9 expression in bladder cancer 39 . By contrast, our study initially identified that miR‐494‐3p was a downstream target of KLF9 and KLF9 positively regulated miR‐494‐3p.…”
Section: Discussionmentioning
confidence: 67%
“…A case in point is that miR‐494‐3p is the upstream gene that represses KLF9 expression in bladder cancer. 39 By contrast, our study initially identified that miR‐494‐3p was a downstream target of KLF9 and KLF9 positively regulated miR‐494‐3p. Interestingly, miR‐494‐3p can be activated by oxidative stress in COPD cell model and its knockdown rescues cell senescence and inflammation.…”
Section: Discussionmentioning
confidence: 69%
“…[31][32][33][34][35] On another note, KLF9 serves as a tumor promoter in nasopharyngeal and ovarian cancers. 36,37 Mechanistically, KLF9 is controlled by microRNAmediated negative regulation or involved in lncRNA-mediated ceRNA network to play a role in cancers, 38,39 and hypermethylation of the KLF9 promoter is instrumental in the prediction of cancer prognosis, 40 and KLF9 mediates the transcription of reactive oxygen species to regulate premalignant hyperplasia. 41 In this study, we uncovered that KLF9 was downregulated in PC cells relative to noncancerous cells and the incorporation of KLF9 in PC cells promoted the proliferation, invasion, and migration.…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factor KLF9 has been widely explored in tumors. For instance, miRNA-494-3p decreased KLF9 expression to facilitate the progression of bladder cancer [38]; KLF9 regulated by TPTEP1/miR-548d-3p axis inhibited cell migration and invasion of gastric cancer [39]; miR-889-5p could downregulate KLF9 expression to accelerate HCC progression [40], which demonstrated that KLF9 had abnormally low expression and KLF9 overexpression generated the suppressing in uence on the progression of tumors including HCC. Here, we explored the downstream target of KLF9.…”
Section: Discussionmentioning
confidence: 99%